Antitumour activity of Annona muricata L. leaf methanol extracts against Ehrlich Ascites Carcinoma and Dalton's Lymphoma Ascites mediated tumours in Swiss albino mice. Issue 1 (1st January 2021) - Naik, Aditi Venkatesh; Dessai, Shanti N.; Sellappan, Krishnan
ABSTRACT: The use of plants as a source of sedative or treatment for cancer is reasonably widespread worldwide. Annona muricata Linn exhibits a vast array of medicinal and ethno-pharmaceutical benefits, attributed by different plant parts. The activity of this plant is regarded to the bio-production of secondary metabolites like alkaloids, phenols, flavonoids, and most unique group of compounds, namely, annonaceous acetogenins. Whilst this plant is gaining popularity as an anticancer treating plant, this study was undertaken to verify the plausible anticancer effect of leaf methanol extracts of A. muricata (LEAM). Acute toxicity study was carried to obtain safe dose in mice models using haematological, biochemical, and histological evaluations in Swiss albino mice. In-vitro cytotoxicity towards Dalton's Lymphoma Ascites (DLA) and Ehrlich Ascites Carcinoma (EAC) cell lines were determined by trypan blue exclusion method. In-vivo antitumour activity of LEAM (100, 200, and 500mg/kg b.wt.) was evaluated using DLA induced solid carcinoma and EAC induced ascites carcinoma models and its comparison with standard drug Cisplatin. Acute toxicity studies did not exhibit significant variations in treated mice suggesting diminutive side effects of LEAM. Statistical analysis revealed the IC50 values for DLA and EAC cell lines as 85.56 ± 5.28 and 68.07 ± 7.39 µg/mL, respectively, indicating better cytotoxic activity against EAC than DLA cells. LEAM decreased the tumour burden in dose-dependent manner. In comparison, with different concentrations tested, treatment with LEAM (200 mg/kg b.wt. and 500 mg/kg b.wt.) significantly reduced the solid tumour volume development by 58.11% and 65.70%, respectively. While lifespan was prolonged up to 51.43% in 500 mg/kg b.wt. LEAM treated ascites tumour-induced mice. This study thus indicates that LEAM possesses potent cytotoxic and antineoplastic activity and calls for more methodical safety assessments and other end-points of anti-tumourigenesis. Abbreviations : LEAM : Leaf methanol extract of Annona muricata; DLA : Dalton's Lymphoma Ascites; EAC : Ehrlich Ascites Carcinoma; IC50 : Half maximal inhibitory concentration; CPCSEA : Committee for the Purpose of Control Supervision of Experiments on Animal; IAEC : Institutional Animal Ethics Committee; ARRIVE : Animal Research: Reporting In-vivo Experiments; DMSO : Dimethyl sulphoxide; LD50 : Lethal Dose, 50%; SD : Standard Deviation; Hb : Haemoglobin; RBC : Red blood cells; WBC : White blood cells; HCT : Hematocrit; MCV : Mean cell volume; MCH : Mean cell haemoglobin; MCHC : Mean cell haemoglobin concentration; SALP : Serum alkaline phosphatase; SGPT : Serum glutamic pyruvic transaminase; SGOT : Serum glutamic oxaloacetic transaminase; ATP : Adenosine triphosphate; EGFR : Epidermal Growth Factor Receptor Graphical abstract: uf0001